2022
DOI: 10.48550/arxiv.2204.06861
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opacity of the highly ionized lanthanides and the effect on the early kilonova

Smaranika Banerjee,
Masaomi Tanaka,
Daiji Kato
et al.

Abstract: We investigate the effect of the presence of lanthanides (Z = 57 − 71) on the kilonova at t ∼ hours after the neutron star merger for the first time. For this purpose, we calculate the atomic structures and the opacities for selected lanthanides: Nd (Z = 60), Sm (Z = 62), and Eu (Z = 63). We consider the ionization degree up to tenth (XI), applicable for the ejecta at t ∼ a few hours after the merger, when the temperature is T ∼ 10 5 K. We find that the opacities for the highly ionized lanthanides are exceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Since the neutron star merger ejecta are highly ionized at an early time (e.g., at around t ∼ 0.1 days, the maximum ionization is ∼ XI, owing to the high temperature of ejecta T ∼ 10 5 K). The atomic opacity calculations for the highly ionized (V -XI) elements has been started relatively recently (e.g., Banerjee et al 2020Banerjee et al , 2022. However, the calculations are limited to the lighter r-process elements (Ca -Ba, Z = 20 − 56, Banerjee et al 2020) and selected rare earth elements (Z = 57 − 71), lanthanides (see Banerjee et al 2022 for atomic opacities of Nd, Z = 60; Sm, Z = 62; and Eu, Z = 63; also see Carvajal Gallego et al 2022aGallego et al ,b, 2023 for the atomic opacities for La -Pm, Z = 57 − 61, ionized to states V -X).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the neutron star merger ejecta are highly ionized at an early time (e.g., at around t ∼ 0.1 days, the maximum ionization is ∼ XI, owing to the high temperature of ejecta T ∼ 10 5 K). The atomic opacity calculations for the highly ionized (V -XI) elements has been started relatively recently (e.g., Banerjee et al 2020Banerjee et al , 2022. However, the calculations are limited to the lighter r-process elements (Ca -Ba, Z = 20 − 56, Banerjee et al 2020) and selected rare earth elements (Z = 57 − 71), lanthanides (see Banerjee et al 2022 for atomic opacities of Nd, Z = 60; Sm, Z = 62; and Eu, Z = 63; also see Carvajal Gallego et al 2022aGallego et al ,b, 2023 for the atomic opacities for La -Pm, Z = 57 − 61, ionized to states V -X).…”
Section: Introductionmentioning
confidence: 99%
“…The atomic opacity calculations for the highly ionized (V -XI) elements has been started relatively recently (e.g., Banerjee et al 2020Banerjee et al , 2022. However, the calculations are limited to the lighter r-process elements (Ca -Ba, Z = 20 − 56, Banerjee et al 2020) and selected rare earth elements (Z = 57 − 71), lanthanides (see Banerjee et al 2022 for atomic opacities of Nd, Z = 60; Sm, Z = 62; and Eu, Z = 63; also see Carvajal Gallego et al 2022aGallego et al ,b, 2023 for the atomic opacities for La -Pm, Z = 57 − 61, ionized to states V -X). The atomic opacity for many of the lanthanides, such as, the lanthanides with Z = 64 − 71, and the post-lanthanide r-process elements (Z > 71, e.g., Wanajo et al 2014) are yet to be included.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to the case of GRB modelling (see Section 4.1), the modelling of KNe can potentially introduce systematic uncertainties on the inclination angle and bias the H 0 value inferred [144]. Our understanding on the physical processes controlling the KN emission is still incomplete and various source of uncertainties are expected to impact the predicted KN emission, including but not limited to the role of the ejecta geometry [145] and r−process heating rates [146], thermalization efficiencies [147] and opacities [148,149]. For instance, Heinzel et al [145] found that the assumption about the ejecta geometry [128,129,140] has a strong impact on the inclination angle, advocating for the inclusion of large systematic uncertainties (∼ 1 mag) when inferring the viewing angle from fits to the KN light curves.…”
Section: Constraints From Kilonova Spectro-photometrymentioning
confidence: 99%
“…Also, another overlooked aspect (of the escaped cocoon) in previous analytical studies is its angular distribution, clearly conical (see Figure 4), instead of the assumed spherical distribution (Nakar & Piran 2017;Piro & Kollmeier 2018). These much lower cocoon masses have many implications on the cocoon emission; they imply that the r-process powered emission is dim (compared to the emission from jet shock heating) making the total timescale of the emission from the escaped cocoon shorter (in the order of seconds to tens of minutes, before the KN emission dominates over); also this implies that the photosphere is smaller and temperature is higher, resulting in an increase in the observed magnitude (i.e., fainter) at optical and UV bands, at a given time [taking κ ∼ 1 cm 2 g −1 Banerjee et al 2020 andBanerjee et al 2022; e.g., see right panel of Figure 3 in Gottlieb et al 2018a]. The trapped cocoon is enclosed by the ejecta and the escaped cocoon, and is effectively unobservable with the KN in the background.…”
Section: Implications On Previous Estimations Of the Cocoon's Cooling...mentioning
confidence: 99%